Assessing the approaches to nausea and vomiting in pregnancy: insights from a nationwide survey of Italian gynecologists (PURITY light) - Romolo Di Iorio; Paola Bianchi; Elena Casolati; Elena Piccolo; Mario Mangrella (Frontiers in Medicine)
IntroductionNausea and vomiting in pregnancy (NVP) affect approximately 70–85% of pregnant women, starting between weeks 6 and 8 and often subsiding by week 20. This study evaluates the therapeutic approaches of Italian gynecologists in the treatment of NVP. In the Italian healthcare system, gynecologists play a central role in prenatal care and are the primary healthcare providers for pregnant women, unlike in other countries where midwives may have a more prominent role.MethodsFrom June to September 2022, a survey of Italian gynecologists was conducted during 15 scientific conferences. The questionnaire collected demographic data and information on clinical practices to support the management of NVP. Statistical analysis assessed the effect of demographic characteristics on clinical behavior.ResultsData from 157 participants, mainly women (72.61%) and professionals from the Public Health System (63.69%), were analyzed. 77.71% always checked NVP during the first visit, based on patients’ reports (84.71%). 54.78% prescribed medication in mild cases, mainly the doxylamine/pyridoxine combination (64.97%).DiscussionThe results show varied practices influenced by demographic and professional factors. Many physicians treat only severe cases of NVP, perceiving it as a transient discomfort, which may lead to poor management. Balanced care is needed to improve the quality of life for pregnant women with NVP.